2021
DOI: 10.1051/e3sconf/202133102013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reproductive health program during disaster in West Sumatra Province

Abstract: Indonesia is one of the countries with the highest disaster risk. Disaster could affect all aspects of human life including reproductive health. The study aims to evaluate reproductive health programs during disasters. The study was conducted with a qualitative study regarding the system approach. There were 19 informants from health centers, disaster management agencies, and social institutions in the South of West Sumatra Province. Data was collected through in-depth interviews, focus group discussions, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Access to a variety of medical and legal services reduces by destructing infrastructure; therefore, before disasters, measures must be taken to increase access to sexual violence services, including mental health services, and integrate them into the disaster response structure( 25 , 28 , 30 - 36 ). To prevent and respond to victims of sexual violence in a timely and appropriate manner, it is necessary to establish super capacity structures for monitoring, response, and referral before occurring disasters ( 28 , 37 - 40 ). Understanding the obligations of responsible organizations and enhancing their preparedness have been acknowledged as essential to being ready for sexual violence ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to a variety of medical and legal services reduces by destructing infrastructure; therefore, before disasters, measures must be taken to increase access to sexual violence services, including mental health services, and integrate them into the disaster response structure( 25 , 28 , 30 - 36 ). To prevent and respond to victims of sexual violence in a timely and appropriate manner, it is necessary to establish super capacity structures for monitoring, response, and referral before occurring disasters ( 28 , 37 - 40 ). Understanding the obligations of responsible organizations and enhancing their preparedness have been acknowledged as essential to being ready for sexual violence ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the taboo nature of sexual violence in many societies, it is necessary to define a mechanism in advance by collecting and sharing information ( 37 , 38 , 48 , 49 ). Other measures of the planning stage that can deliver quality services and speed up the process include allocating resources and funds to victims of sexual assault and providing the appropriate tools ( 24 , 34 , 40 ). Studies have shown that the distribution of health equipment among people in disaster-affected areas can reduce the likelihood of sexual violence.…”
Section: Resultsmentioning
confidence: 99%